Market Power : Airports - Vertical Integration between Airports and Airlines - Serebrisky, Tomás (World Bank, Washington, DC, 2012)
In the late 1980s and the 1990s many countries privatized airports or concessioned their operation. The United Kingdom began the trend, followed by other countries adopting new forms of infrastructure ownership and management. To control infrastructure licensing and the "natural monopoly" characteristics of some airport services, governments developed regulatory policies for airport systems. The operation of an airport creates incentives to transfer the airport's market power to the air transport market. If the airport market is regulated but the airport operator is allowed to control at least one airline, those incentives can give rise to anticompetitive practices aimed at displacing competing airlines. When the regulatory framework for airports lacks explicit rules about such vertical integration, that can have consequences for competition in the air transport market. Australia and Chile, for example, have an explicit prohibition on vertical integration. By contrast, Argentina has no restrictions on vertical integration leaving it to the antitrust agency to decide whether to approve or reject a vertical merger. Airlines provide air transport services by combining aircraft, personnel, airport services, and other inputs. Airports supply a series of services to air transport companies and to passengers. Aeronautical services (rescue, security, firefighting, infrastructure supply, runway and taxiway maintenance). Aeronautical-related commercial services (catering; supply of fuel and lubricants; baggage, passenger, and aircraft assistance). Commercial services (banks, hotels, restaurants, car rental, car parking, retail shops, duty-free shops).